NAVIGATING THESIS WRITING: CHALLENGES FACED BY EFL STUDENTS IN AN ENGLISH DEPARTMENT - Jusmin HJ Wahid; Nurlaily Sofyan; Iwan Irawan; Siti Nahla Hamim (University of Kuningan, 2024)
The preparation of the scientific essay (thesis) is the last phase in carrying out the duties as a student; the thesis itself is a scientific essay that must be written by a student as part of his/her academic final requirements. This research is qualitative research with a case study approach; qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects. The subjects of this study were English Education Students at Muhammadiyah University, North Maluku. The results of questionnaire statements and interviews found that the factors caused the students difficulties in writing scientific essay (thesis) were internal factors include students' understanding of grammar and students' ability to write thesis while external factors are from the environment which includes family, friends, and economic factors.